2010
DOI: 10.3748/wjg.v16.i39.4968
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and long-term outcome of extrahepatic portal vein obstruction in children

Abstract: EHPVO is a rare disorder. The etiological factors are still mostly unknown, and the endoscopic and surgical treatment options ensure a good long-term prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
47
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 21 publications
9
47
1
5
Order By: Relevance
“…As observed in the present study, PVT does not show gender predominance and its more common initial manifestations in children are upper gastrointestinal bleeding and splenomegaly, which corroborates results reported in the literature (1,6,41,47,50,53) . In the present casuistic, upper gastrointestinal bleeding was the main initial clinical manifestation in 52.7% of patients, followed by splenomegaly in 36.4%.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…As observed in the present study, PVT does not show gender predominance and its more common initial manifestations in children are upper gastrointestinal bleeding and splenomegaly, which corroborates results reported in the literature (1,6,41,47,50,53) . In the present casuistic, upper gastrointestinal bleeding was the main initial clinical manifestation in 52.7% of patients, followed by splenomegaly in 36.4%.…”
Section: Discussionsupporting
confidence: 81%
“…(1) and Weiss et al (53) reported a greater proportion of patients with splenomegaly as the initial finding (63% and 43.3%, respectively). Thus, the possibility of PVT should be raised and a Doppler ultrasound exam should be requested in children and adolescents with UGIB or isolated finding of splenomegaly during the clinical exam.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations